Comparison of the effects of hemoporfin-mediated photodynamic and Vbeam pulsed dye laser in the treatment of port-wine stains: a retrospective analysis - Yantao Ding; Can Jin; Xinyu Liang; Jiajie Chen; Shengxiu Liu (European Journal of Medical Research)
Abstract Background The pulsed dye laser (PDL) is widely regarded as the gold standard treatment for port wine stain (PWS); however, its therapeutic efficacy exhibits considerable variability. Recent research indicates that hemoglobin-mediated photodynamic therapy (HMME–PDT) is emerging as a highly promising treatment modality for PWS. This retrospective study aims to evaluate and compare the clinical efficacy and safety profiles of HMME–PDT and 595 nm-PDL in the management of PWS. Methods This study retrospectively analyzed a total of 850 patients with PWS treated with 595 nm-PDL and 279 patients with PWS treated with HMME–PDT at the Skin Laser Beauty Center of the First Affiliated Hospital of Anhui Medical University from January 2015 to December 2024. Results In total, the cure rate, the total significant response rate, and the total response rate were 22.22%, 54.12%, and 88.89%, respectively, in the HMME–PDT group, which were obviously higher than those in the 595 nm PDL group (9.65%, 31.29%, and 68.94%, respectively) with the P values as 0.001, 0.001, and 0.001. After total treatments, the different subtype and location had different responses to 595 nm-PDL, the different age and locations had different responses to HMME–PDT. Generally speaking, the therapeutic effect of HMME–PDT was better than that of PDL therapy under the different number of treatments. Conclusions Both 595 nm-PDL and HMME–PDT demonstrate significant efficacy in the treatment of PWS. Our single-center retrospective study indicated that HMME–PDT may offer superior efficacy compared to 595 nm–PDL treatment. Further research is warranted to fully elucidate the true value of HMME–PDT and 595 nm-PDL for PWS.